The Effect of Capital Structure on Financial Performance with Firm Size as a Moderating Variable of Non-Financial Firms Listed at the Nairobi Securities Exchange - Kerongo Meshack; Winnie Nyamute; Kennedy Okiro; Elly Duncan (European Scientific Journal, ESJ, 2020)
This paper examines the effect of capital structure on the financial performance of the non-financial firms listed at the Nairobi Securities Exchange and how this relationship is moderated by firm size. In addition, the paper evaluates the existence of equilibrium and disequilibrium relationship among the variables. The study analyzed unbalanced panel data sourced from across 53 non-financial firms listed at the Nairobi Securities Exchange which covers the period from 2010 to 2017. Total debt to total equity, total equity to total assets, and total debt to total assets were used for assessing capital structure of the listed non-financial firms. Firm size was measured using natural logarithm of total sales. Financial performance attribute was measured by Tobin’s Q. Data was analyzed using descriptive statistics, multiple and simple regression analysis. Regression analysis was used to ascertain the direction and magnitude of the relationships. The study revealed that leverage had a significant positive effect on the financial performance of the NSE listed non-financial firms. Furthermore, firm size has a positive moderating effect on the relationship between capital structure and financial performance. The study concludes that firms should strive to increase their leverage since it has a statistically significant positive effect on financial performance of the nonfinancial firms listed on the NSE. The study further concludes that firms should strive to grow their firm size by increasing their total sales. This is because it has a statistically significant positive effect on the financial performance of NSE listed non-financial firms.